Investigating brain D-serine: advocacy for good practices - Mothet, Jean-Pierre (Acta Physiol (Oxf), 2019)
The last two decades have witnessed remarkable advance in our understaning the role of D-amino acids in the mammalian nervous system: from the unknown, to known molecules with unknown functions, to potential central players in health and disease. D-Amino acids have emerged as an important class of signaling molecules. In particular, the exploration of the roles of D-serine in brain physiopathology is a vibrant field that is growing at an accelerating pace. However, disentangling the functions of a small chiral molecule in the complex chemical milieu of the brain requires to be familiar with distinct measurement approaches but also to currently work with delicate molecular tools which effects can be confounded. Thus, study of D-amino acids requires accurate methodologies and specific controls, and these have often been lacking. Here we outline best practices for D-amino acid research, with a special emphasis on D-serine. We hope these concepts help move the field to greater rigor and reproducibility, allowing the field to advance.